2020
DOI: 10.1038/s41467-020-14632-2
|View full text |Cite
|
Sign up to set email alerts
|

Stroma remodeling and reduced cell division define durable response to PD-1 blockade in melanoma

Abstract: Although immune checkpoint inhibitors (ICIs) have achieved unprecedented results in melanoma, the biological features of the durable responses initiated by these drugs remain unknown. Here we show the genetic and phenotypic changes induced by treatment with programmed cell death-1 (PD-1) blockade in a genetically engineered mouse model of melanoma driven by oncogenic BRAF. In this controlled system anti-PD-1 treatment yields responses in ~35% of the tumors, and prolongs survival in ~27% of the animals. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…GO203, targeting MUC1-C, can suppress PD-L1 expression of NSCLC and breast cancer, and induces effectors of innate and adaptive immunity, resulting in improve anticancer effects [31] We determined that evodiamine can block PD-L1 expression on mRNA and protein levels, perhaps through inhibiting the MUC1-C. Silencing MUC1-C in H1975 decreases apoptosis following evodiamine treatment. Currently, several preclinical and clinical trials for the combination of other therapy with immune inhibitors in the treatment patients reveal biomarkers of response and resistance to anti-PD-1 monotherapy and combined anti-CTLA-4 and anti-PD-1 immunotherapy, significantly improve the anti-tumor effect [6,[58][59][60][61]. Collectively, the combination of evodiamine and PD-1 mAb treatment enhance anti-cancer and survival in a Lewis lung carcinoma model.…”
Section: Discussionmentioning
confidence: 99%
“…GO203, targeting MUC1-C, can suppress PD-L1 expression of NSCLC and breast cancer, and induces effectors of innate and adaptive immunity, resulting in improve anticancer effects [31] We determined that evodiamine can block PD-L1 expression on mRNA and protein levels, perhaps through inhibiting the MUC1-C. Silencing MUC1-C in H1975 decreases apoptosis following evodiamine treatment. Currently, several preclinical and clinical trials for the combination of other therapy with immune inhibitors in the treatment patients reveal biomarkers of response and resistance to anti-PD-1 monotherapy and combined anti-CTLA-4 and anti-PD-1 immunotherapy, significantly improve the anti-tumor effect [6,[58][59][60][61]. Collectively, the combination of evodiamine and PD-1 mAb treatment enhance anti-cancer and survival in a Lewis lung carcinoma model.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between tumor cells and CAFs may cause treatment failure (Errarte et al, 2020 ). CAFs promote tumor matrix deposition and remodeling in the TME (Sahai et al, 2020 ), help cancer cells evade immune surveillance (De Jaeghere et al, 2019 ), and achieve resistance to immunotherapy (Galvani et al, 2020 ). A study showed that the extracellular matrix could reduce the effectiveness of immune checkpoint blockers (Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between tumor cells and CAFs may be the cause of treatment failure [24]. CAFs promote tumor matrix deposition and remodeling in the TME [25], help cancer cells evade immune surveillance [26], and achieve resistance to immunotherapy [27]. A study showed that the extracellular matrix can reduce the effectiveness of immune checkpoint blockers [28].…”
Section: Discussionmentioning
confidence: 99%